Rancang Bangun Sistem Cetak Faktur Penjualan Berbasis Website pada PT. Akusara Mitra Sinergi Semarang - Jovan, Tjia, Marcelino; Widayati, Yohana Tri; Bakti, Cristeddy Asa (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2025)
This research aims to design a website-based sales invoice printing system to overcome the problems of complexity and limitations in using MS. Excel at PT Akusara Mitra Sinergi Semarang. This research uses the Waterfall system development method and also the UML (Unified Modeling Language) model in designing a sales invoice printing system. In this design, using the CodeIgniter framework program or in the PHP programming language, HTML, and MySQL database to store data. The main features provided include creating, managing, printing invoices, and setting invoice numbers. Based on the results of the design, the system succeeded in increasing the speed and accuracy of the invoicing process, as well as minimizing human error. Thus, this system is expected to support PT Akusara Mitra Sinergi Semarang in achieving higher operational efficiency and strengthening overall business performance.